Critical theory diverse objects, diverse subjects - Lehmann, Jennifer M., 1956- (New York : JAI, 2003)
The contributions in this 22nd volume of "Current Perspectives in Social Theory" explore the arguments for and against a view of the world in which multiple, distinct and conflicting societies differ both over time and contemporaneously.
Part I: Bringing Marxism back ... with Foucault -- Foucoult's encounter with Marxism / Paul Paolucci -- Part II: Critical theories of knowledge: epistemology and culture -- Afrocentricity and the Eurocentric hegemony of knowledge: contradictions of place / Molefi Kete Asante -- Epistemology, culture and rhetoric: some social implications of human cognition / Thomas J. Burns and Terri LeMoyne -- Films and utopia: the culture industry revisited / James J. Dowd -- Part III: Social structures, theories and movements -- Cybercritique: a social theory of online agency and virtual structures / Timothy W. Luke -- Rationalism and traditionalism in classical sociology and contemporary feminist theory / Mary Godwyn -- The duality of systems: networks as media and outcomes of movement mobilization / Jeff Livesay -- Part IV: Bridging the African diaspora in the new millennium (selected papers from the eponymous conference at the University of Nebraska, Februrary 2001) -- Re-visioning race: dismantling whiteness / Gerise Herndon -- The phychological and spiritual implications of western Christian missionaries' influence on the African diaspora: special reference to West African countries / Joshua Olayiwola Oyekan -- Part V: Critical theory (selected papers from the Conference of the Socialogical Theory Section, International Socialogical Association, University of Cambridge, September 2000) -- How is society possible? Towards a metacritique of reification / Frédéric Vandenberghe -- The form of difference: reimagining critical theory / Nancy Weiss Hanrahan -- Prolegomena to an intercultural critical theory / Fuyuki Kurasawa -- Pragmatism versus socialogical hermeneutics / Patrick Baert -- Subjectivity, culture, autonomy: Castadoriadis and social theory / Anthony Elliott.
Description based on print version record.
Keywords: Social sciences -- Philosophy; Knowledge, Theory of; Social theory; Social Science -- Sociology -- General